2018
DOI: 10.4103/ortho.ijortho_304_17
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Elastic Nailing with Temporary External Fixator versus Bridge Plating in Comminuted Pediatric Femoral Shaft Fractures: A Comparative Study

Abstract: Background:High-velocity trauma, associated injuries, risk of iatrogenic devascularization of fragments and need for maintaining alignment upto union make comminuted fracture in pediatric femur a formidable fracture to treat. This comparative study was conducted to evaluate the outcomes of two modes of management in such cases: titanium elastic nailing supplemented with external fixator and submuscular bridge plating (BP).Materials and Methods:Thirty eight children (aged 6–12 years) with comminuted fracture sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In a previous study, 24 patients who were treated for femoral shaft fracture were evaluated retrospectively and although varus deformity developed in four patients and procurvatum deformity was seen in one patient after radiographic healing, no clinical effect was determined because all deformities were <10° (25). In a similar study, means of 5° varus and 5.4° procurvatum deformity were observed after radiographic recovery in the patient group treated with TEN, but these results did not reflect negatively on the clinical results (23). In another study, 30 patients treated by the TEN method were evaluated retrospectively, and although an average of 3.2° varus, 0.53° valgus, and 2.4° procurvatum deformities and a mean of 0.71 cm LLD were detected, none of the patients were functionally affected (26).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous study, 24 patients who were treated for femoral shaft fracture were evaluated retrospectively and although varus deformity developed in four patients and procurvatum deformity was seen in one patient after radiographic healing, no clinical effect was determined because all deformities were <10° (25). In a similar study, means of 5° varus and 5.4° procurvatum deformity were observed after radiographic recovery in the patient group treated with TEN, but these results did not reflect negatively on the clinical results (23). In another study, 30 patients treated by the TEN method were evaluated retrospectively, and although an average of 3.2° varus, 0.53° valgus, and 2.4° procurvatum deformities and a mean of 0.71 cm LLD were detected, none of the patients were functionally affected (26).…”
Section: Discussionmentioning
confidence: 91%
“…In another study, it was reported that open reduction and plate fixation should be avoided in the treatment of pediatric femoral shaft fractures because excessive soft tissue dissection leads to displacement of the fracture line (3). In another study, 38 patients with femoral shaft fractures treated with TEN or bridge plating were evaluated; no significant difference was found between the two groups functionally or radiologically and acceptable results were obtained (23). In a similar study, 65 patients treated with TEN or sub muscular plating were retrospectively examined and although functionally and radiologically equivalent results were found, the duration of surgery, blood loss during surgery and hospital costs were significantly higher in the group treated with sub muscular plating (24).…”
Section: Discussionmentioning
confidence: 99%
“…The mean duration of hospitalization was 3.7 ± 1.4 days (range, 2-7). The mean follow-up time was 21.8 ± 2.7 months (range, [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Even so, to the best of our knowledge, this is the first study that has evaluated the clinical and radiological outcomes of UFSF in children between 5 and 11 years of age managed by the combined use of ESIN and temporary EF. The retrospective nature of our study is prone to selection and observational biases, and randomization was not possible; however, the patients were consecutive, all came from a single institution, and the total number of cases was higher than those in other published studies ( 29 , 30 ). Finally, the retrospective nature of our study also limited the level of evidence for the findings, as our series lacks a control group treated with other surgical techniques.…”
Section: Discussionmentioning
confidence: 96%
“…Several implants for managing pediatric fractures are now available. 13 One must not forget that simpler implants might work as efficiently as bulky ones for pediatric fractures, if used appropriately. Hip spica is fairly well tolerated in children and one should not be hesitant in its use, if indicated.…”
mentioning
confidence: 99%